Improving of fuel quality and environment using new synthetic (Mn3O4/AC-nano-particles) for oxidative desulfurization using digital baffle batch reactor - Amer T. Nawaf; Jasim I. Humadi; Ali A. Hassan; Mohamed A. Habila; Rajesh Haldhar (South African Journal of Chemical Engineering)
This experimental study uses a modified homemade novel nano-catalyst (8 %Mn3O4/AC-nanoparticles) to explore the oxidative desulfurization (ODS) process in a digital baffle batch reactor (DBBR) to remove sulfur compounds from light gas oil. With its efficient impregnation, high activity, excellent distribution of pore sizes, and increased surface area, the manganese oxide nano-catalyst design supported on activated nanoparticles exhibits exceptional catalytic performance. To gain a greater understanding of the ODS process, moderate operating conditions are used at various reaction temperatures, reaction times, and oxidant amounts. Results of the experiment indicate that increasing the temperature, batch reaction, and oxidant quantity increases the conversion of sulfur compounds. It has been determined that the novel nano-catalysts are 93.33 % effective at removing sulfur at a reaction temperature of 90 °C, a batch time of 45 min, and an oxidant agent amount of 5 ml from H2O2.